GIVING VOICE TO OUR CORE FRENCH STUDENTS: IMPLICATIONS FOR ATTRITION AND THE DISCOURSE ON THE BENEFITS OF LEARNING FSL IN ONTARIO - Arnott, Stephanie (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2020)
This article explores student motivation to learn French as a second language (FSL) in school. Ontario Grade 9 students (N = 63) were surveyed on their intention to (dis)continue studying French in the Core French (CF) program in Grade 10 when FSL becomes optional. Survey participants shared their reasoning, and a subset (n = 7) took part in a focus group. Although motivating factors to (dis)continue in CF align with previous studies, participants openly contemplated the relevance of these factors to their lives. In response, this article explores the discourse on the benefits of learning French and debates its applicability to adolescent FSL learners. The implications for efforts to address CF attrition and promote FSL learning are also discussed. DONNER LA PAROLE À NOS ÉLÈVES DE FRANÇAIS DE BASE : IMPLICATIONS POUR L'ATTRITION ET LE DISCOURS SUR LES AVANTAGES DE L'APPRENTISSAGE DU FLS EN ONTARIO Cet article explore la motivation des élèves à apprendre le français, langue seconde (FLS), à l'école. Des élèves de 9e année de l'Ontario (N = 63) ont été interrogés sur leur intention de continuer ou de mettre un terme à leur étude du français dans le programme de base (CF) en 10e année lorsque la matière devient facultative. Les participants à l'enquête ont partagé leur raisonnement, et un sous-ensemble (n = 7) a participé à un groupe de discussion. Bien que les facteurs de motivation pour continuer ou cesser le CF sont conformes aux études précédentes, les participants ont ouvertement envisagé la pertinence de ces facteurs dans leur vie. En réponse, cet article explore le discours sur les avantages de l'apprentissage du français et débat de son applicabilité aux adolescents apprenant le FLS. Les implications pour les efforts abordant l'attrition des élèves du CF et la promotion de l'apprentissage du FLS sont également discutées.